Enhancement in soil fertility, early plant growth and nutrition and mycorrhizal colonization by vermicompost application varies with native and exotic tree species - Xue, Jianming; Bakker, Mark R.; Milin, Sylvie; Graham, Doug (Journal of soils and sediments, 2022)
Purpose The impact of vermicompost on tree-soil systems is not yet fully understood. This study aimed to comparatively investigate the effects of chemical fertilizer, compost and vermicompost on soil enzymatic activities, seedling mycorrhizal colonization, growth and nutrition of one exotic tree species (radiata pine, Pinus radiata D. Don) and two native tree species (mānuka, Leptospermum scoparium and tōtara, Podocarpus totara ). Methods A 12-month-long pot trial was set up in the glasshouse with a factorial design of three tree species (radiata pine, tōtara and manuka) by six treatments, including T1-control, T2-chemical fertilizer, T3-HS compost, T4-HS vermicompost, T5-LS vermicompost and T6-CM vermicompost. We assessed the main effects and interactions of treatment and species on soil chemical and biological properties, plant growth and nutritional responses. Results Compared to the untreated control (T1), application of vermicomposts (T4-T6) and compost (T3) significantly improved soil chemical properties and enzymatic activities, and increased total seedling dry weight by 160–260%, shoot concentrations of nitrogen (N) by 54–97% and phosphorus (P) by 61–91%. Vermicomposts were comparable to diammonium phosphate (DAP) applied at 133 kg N ha −1 (T2) in stimulating the growth of native species (mānuka and tōtara) without negative impact on mycorrhizal colonization, with T5 being better than DAP (T2) in promoting mānuka growth. However, application of vermicompost alone was less effective than DAP in stimulating the exotic radiata pine growth. Overall, soil activities of dehydrogenase, urease, acid phosphatase and invertase were significantly and positively correlated to total C and N and exchangeable Ca and Mg. Conclusion The increased growth of three tree species after application of vermicomposts was mainly related to improved N and P nutrition associated with enhanced root growth and soil enzymatic activities. Our findings imply that the vermicomposting products from septic tank waste could be a promising alternative to inorganic fertilizers in land application or greenhouse potting media of native tree species.